2005
DOI: 10.1093/hmg/ddi159
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ZMPSTE24 (FACE-1) causes autosomal recessive restrictive dermopathy and accumulation of Lamin A precursors

Abstract: Restrictive dermopathy (RD) is characterized by intrauterine growth retardation, tight and rigid skin with prominent superficial vessels, bone mineralization defects, dysplastic clavicles, arthrogryposis and early neonatal death. In two patients affected with RD, we recently reported two different heterozygous splicing mutations in the LMNA gene, leading to the production and accumulation of truncated Prelamin A. In other patients, a single nucleotide insertion was identified in ZMPSTE24. This variation is loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 263 publications
(253 citation statements)
references
References 33 publications
3
248
1
1
Order By: Relevance
“…11,[14][15][16]21,22 Using specific macros on ImageJ, we then analyzed the ratio of abnormal nuclei, based on DAPI staining in at least 100 cells, for patients 1 and 2, an HGPS patient and a healthy control. No differences were observed between patients' cells regarding the circularity (0.83 for HGPS, 0.78 for P1 and 0.80 for P2) but all patients presented a significantly higher level of circular nuclei in contrast to control cells (0.69% for control).…”
Section: Deleted Prelamin a Isoform Identificationmentioning
confidence: 99%
“…11,[14][15][16]21,22 Using specific macros on ImageJ, we then analyzed the ratio of abnormal nuclei, based on DAPI staining in at least 100 cells, for patients 1 and 2, an HGPS patient and a healthy control. No differences were observed between patients' cells regarding the circularity (0.83 for HGPS, 0.78 for P1 and 0.80 for P2) but all patients presented a significantly higher level of circular nuclei in contrast to control cells (0.69% for control).…”
Section: Deleted Prelamin a Isoform Identificationmentioning
confidence: 99%
“…Recessive mutations resulting in complete absence of ZMPSTE24 cause restrictive dermopathy, which is characterized by intrauterine growth retardation, rigid or tight skin with prominent superficial vessels, defects in bone mineralization, dysplastic clavicles, and early postnatal death [72,73]. Hypomorphic ZMPSTE24 alleles can lead to the accumulation of some unprocessed prelamin A in addition to mature lamin A, indicating residual activity of the mutated ZMPSTE24 protein.…”
Section: The Secondary Laminopathiesmentioning
confidence: 99%
“…Intriguingly, mice with complete loss of Zmpste24 do not develop the severe disease in human patients with restrictive dermopathy that is associated with perinatal death [73]. A study of Zmpste24 −/− mice revealed that ZMPSTE24 is absolutely required for the processing of farnesyl-prelamin A to mature lamin A [68,69].…”
Section: Zmpste24-deficient Micementioning
confidence: 99%
“…1,2 In the original study, we were able to identify that this early lethal disorder is caused by lamin A-specific defects either due to dominant LMNA mutations or, in most cases, to recessive ZMPSTE24 null mutations. 1,3 Lamins are ubiquitous nuclear proteins constituting the type V intermediate filaments subfamily; they are subdivided in A-and B-type lamins, respectively encoded by the LMNA, LMNB1 or LMNB2 genes (OMIM reference #: 150330, 150340, 150341). 4,5 Lamins are major components of the nuclear lamina, a filamentous meshwork underlying the inner nuclear membrane involved in nuclear shape, nuclear pore complex spacing and resistance to mechanical stress.…”
Section: Introductionmentioning
confidence: 99%